Maximizing Biocatalytic Cyclohexane Hydroxylation by Modulating Cytochrome P450 Monooxygenase Expression in P. taiwanensis VLB120 - Schäfer, Lisa; Karande, Rohan; Bühler, Bruno (Frontiers in Bioengineering and Biotechnology, 2020)
Cytochrome P450 monooxygenases (Cyps) effectively catalyze the regiospecific oxyfunctionalization of inert C-H bonds under mild conditions. Due to their cofactor dependency and instability in isolated form, oxygenases are preferably applied in living microbial cells with Pseudomonas strains constituting potent host organisms for Cyps. This study presents a holistic genetic engineering approach, considering gene dosage, transcriptional, and translational levels, to engineer an effective Cyp-based whole-cell biocatalyst, building on recombinant Pseudomonas taiwanensis VLB120 for cyclohexane hydroxylation. A lac-based regulation system turned out to be favorable in terms of orthogonality to the host regulatory network and enabled a remarkable specific whole-cell activity of 34 U gCDW-1. The evaluation of different ribosomal binding sites revealed that a moderate translation rate was favorable in terms of the specific activity. An increase in gene dosage did only slightly elevate the hydroxylation activity, but severely impaired growth and resulted in a large fraction of inactive Cyp. Finally, the introduction of a terminator reduced leakiness. The optimized strain P. taiwanensis VLB120 pSEVA_Cyp allowed for a hydroxylation activity of 55 U gCDW-1. Applying 5 mM cyclohexane, molar conversion and biomass-specific yields of 82.5 % and 2.46 mmol cyclohexanol gbiomass-1 were achieved, respectively. The strain now serves as a platform to design in vivo cascades and bioprocesses for the production of polymer building blocks such as ε-caprolactone.